Significantly higher frequency of Helicobacter suis in patients with idiopathic parkinsonism than in control patients. Issue 11 (5th October 2013) - Blaecher, C.; Smet, A.; Flahou, B.; Pasmans, F.; Ducatelle, R.; Taylor, D.; Weller, C.; Bjarnason, I.; Charlett, A.; Lawson, A. J.; Dobbs, R. J.; Dobbs, S. M.; et al.
Summary: Background: There is increased proportional mortality from Parkinson's disease amongst livestock farmers. The hypokinesia of Parkinson's disease has been linked to Helicobacter pylori. H. suis is the most common zoonotic helicobacter in man. Aim: To compare the frequency of H. suis, relative to H. pylori, in gastric biopsies of patients with idiopathic parkinsonism (IP) and controls from gastroenterology services. Methods: DNA extracts, archived at a Helicobacter Reference Laboratory, from IP patient and gastroenterology service biopsies were examined anonymously for H. suis, using species‐specific RT‐PCR. Results: Relative risk of having H. suis in 60 IP patients compared with 256 controls was 10 times greater than that of having H. pylori . In patients with IP and controls, respectively, frequencies of H. suis were 27 (exact binomial 95% C.I. 15, 38) and 2 (0, 3)%, and of H. pylori, 28 (17, 40) and 16 (12, 21)%. Excess of H. suis in IP held when only the antral or corporal biopsy was considered. Of 16 IP patients with H. suis, 11 were from 19 with proven H. pylori eradication, 3 from 17 pre‐ H. pylori eradication, 2 from 24 H. pylori culture/PCR‐negative. Frequency was different between groups ( P = 0.001), greatest where H. pylori had been eradicated. Even without known exposure to anti‐ H. pylori therapy, H. suis was more frequent in IP patients (5/41) than in controls (1/155) ( P = 0.002). Partial multilocus sequence typing confirmed that strains from IP patients (6) and control (1) differed from RT‐PCR standard strain. Conclusions: Greater frequency of H. suis in idiopathic parkinsonism appears exaggerated following H. pylori eradication. Multilocus sequence testing comparison with porcine strains may clarify whether transmission is from pigs/porcine products or of human‐adapted, H. suis ‐like, bacteria.